RADIKALISME ISLAM: STUDI DOKTRIN KHAWARIJ - Puadi, Hairul (LPPI Universitas Al-Qolam Malang, 2016)
Khawarij’s main doctrine is the doctrine of takfir. For this sect, those who do not determine the law according to the Qur'an is kafir. So are those who perpetrated a great sin that they have to be killed or combated. However, Khawarij also has some fairly nuanced subsects, from ones whose understanding of the hardest, such as al-Azariqah, until slightly soft, like al-Sufriyah. Historical, socio-cultural, geographical and psychological factors had form Khawarij’s doctrines into radical, fanatic and anti-compromise. Historically, Khawarij sect born from hard friction between Ali and Mu’awiyah. In socio-cultural and geographical sphere, this group comes from Bedouin tribes who live in the barren and arid desert thus forging a strong character. In addition, the geographic position, away from the center of civilization, had form insular insight. The radicality also caused by the psychological elements that appear as a result of the rejection of their proposals against Ali to cancel arbitration with Mu'awiyah. This rejection has aroused their hurt and grudge so that they are against any person or any government who is not among their group. Keywords: Khawarij, takfir, doctrines, radical